PERLINDUNGAN HUKUM BAGI KONSUMEN BERKAITAN DENGAN PENERAPAN TIMBANGAN PADA BERAS ECERAN DI KOTA DUMAI - Cristina, Mawar; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Cales are the most common type of measuring instrument in trading andbuying and selling. In buying and selling transaction activities, scales are used asbenchmarks to ensure the accuracy of the content and weight of the goods beingtraded. There is often a loss experienced by consumers in trade transactions thatis not in accordance with the application of retail rice scales purchased byconsumers from traders.The problems and objectives to be discussed in this paper are to find out thelegal protection for consumers related to the application of scales on retail rice inthe city of Dumai and to find out the form of responsibility of business actors toconsumers who suffer losses due to fraudulent practices of misuse of scales onretail sale in Dumai City. The location of the study was carried out at the existingshop at the Dumai Timur sub-district, Kapur Hill, South Dumai. This type ofresearch is sociological juridical research, while the nature is descriptive. Thedata sources in this study were obtained through primary and secondary data.Data collection techniques carried out in this paper use interviews,questionnaires and library studies. the data analysis techniques the author didwith qualitative analysis.After being described and discussed in this thesis, it can be concluded thatlegal protection for consumers relating to the application of scales on retail ricein Dumai City for correct and honest information regarding the weighing of riceby traders for consumers has not fully improved, because there are still tradersstill cheating on weighing goods in the community / consumer environment. Basedon Article 19 of Law Number 8 of 1999 concerning Consumer Protection, shopmerchants who use scales are responsible for providing compensation orcompensation for the loss of consu.mers buying retail rice. but in fact, there is stillfraud in the retail rice weighing carried out by traders in the community. but theydo not carry out their responsibilities properly.Keywords: Scales - Traders - consumers - stalls